Popis by HanifMZ / Nurshaheera Fatiniafza Alias - Alias, Nurshaheera Fatiniafza (2020)
This case study is to fulfil the task of ENT300, Fundamentals of the Entrepreneurship. In this case study, I need to collect all the information regarding the business profile that I choose. The business that I choose for this case study is Popis by HanifMZ. Popis or known as Popia Pisang which is brand under HanifMZ is founded by Muhammad Hanif Mat Zin. For further information, the owner was an alumni from Universiti Teknologi Mara, graduated from Bachelor Hons (Sc) Chemistry. Popis by HanifMZ is located at Batu Rakit, Terengganu. Popia Pisang or Popis is a food based of banana. This is the example of a creative entrepreneur. Besides that, with the opening of the store, it will help the local people to earn money. This is because they provide the job opportunity to the local people.